EVALAUATION OF THE COMPONENTS AND ANTIMICROBIAL ACTIVITY OF VOLATILE OIL FROM ZANTHOXYLUMLIMONELLA FRUIT. - ARUNKUMARK.V; M.PARIDHAVI (International Journal of Pharma and Bio Sciences, 2013)
Essential oils constitute a relatively common group of natural products present in aromatic medicinal plants. They are volatile liquids usually with pleasant and sometimes intensive odors (aroma).Essential oils are well known for its activity in lungs related diseases.They maintained the ventilation and drainage of the sinuses, had an anti-inflammatory effect on the trachea5 and reduced asthma.The essential oil isolated from Zanthoxylumlimonellawere proved a large number of compounds. Many compounds were detected and proved by previous workers, some of them yet to be identified and screened.Traditional usage of the plant indicates various uses even some are contradictory.In the present study showed that the oil is moderately active against gram-positive and significantly no action against gram-negative.